2023
DOI: 10.1007/s10792-023-02675-5
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcomes of patients presenting to Sydney Eye Hospital with neovascular glaucoma

Abstract: Background Neovascular glaucoma (NVG) is a sight-threatening condition that is often refractory to treatment. Current management principles are yet to be standardized due to lack of evidence. We studied the interventions used to treat NVG at Sydney Eye Hospital (SEH) and the two-year surgical outcomes. Methods We performed a retrospective audit of 67 eyes of 58 patients with NVG from January 1, 2013, to December 31, 2018. Intraocular pressure (IOP), best-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The retrospective nature of our study did not allow for further differentiation between causes in this patient cohort with already severely compromised visual functions. Neovascular glaucoma and silicone oil induced glaucoma already pose a higher risk of vison loss [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective nature of our study did not allow for further differentiation between causes in this patient cohort with already severely compromised visual functions. Neovascular glaucoma and silicone oil induced glaucoma already pose a higher risk of vison loss [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported a notable association between glaucoma, specifically open-angle glaucoma, and an increased incidence of retinal vascular occlusions [141,142]. In a comprehensive Korean nationwide population-based retrospective study, it was observed that individuals diagnosed with open-angle glaucoma exhibited a significantly elevated incidence of retinal vascular occlusions when compared to the general population [20].…”
Section: Glaucoma Is a Risk Factor For Retinal Vascular Occlusionsmentioning
confidence: 99%